Modelling for performance prediction of highly insulated buildings with different types of thermal mass. (25th July 2017) - Siddiqui, O.; Kumar, R.; Fung, A.S.; Zhang, D.; White, M.A.; Whitman, C.A.
Highlights: TRNSYS modelling for performance prediction of highly insulated buildings. The impact of thermal mass on the energy saving and occupant comfort was studied. The thermal masses were found to contribute to energy savings of 10–15%. The thermal mass was adding considerably to the comfort of the occupants. Abstract: Thermal performances of two phase change materials (PCM) in the Toronto's Net-Zero Energy House are compared and contrasted with commonly available forms of thermal mass. TRNSYS simulations show that the use of thermal mass was found to contribute to energy savings of 10–15% when different types of thermal mass were mixed into the building envelope. The results exhibit that the performance of a novel solid-solid phase PCMs, recently developed by researchers at Dalhousie University and known as DalHSM-1, could be comparable to a commercially available PCM from BASF (Micronal) in the heating mode. The cooling mode performance revealed that DalHSM-1 provided lower energy savings when compared to Micronal, due to a lower phase transition temperature and latent heat. The impact of thermal mass on the occupant comfort was also investigated by considering the total number of hours where the temperature exceeded the heating set point of 21 °C. The results showed that the total number of hours where the temperature exceeded 21 °C could be reduced significantly with different types of thermal mass, thus contributing considerably to the comfort of the occupants.